2005
DOI: 10.1038/sj.cr.7290273
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of rat chondrocyte proliferation: studies in embryo, adult and osteoarthritic (OA) cartilage

Abstract: The aim of this work was to study the ontogeny of chondrocyte cell division using embryo, adult and osteoarthritic (OA) cartilage. We searched for mitosis phases and performed a comparative evaluation of mitotic index, basic fibroblast growth factor b (FGFb), transforming growth factor β1 (TGF-β1) receptors, cyclin dependent kinase (CDK1) and Cyclin-B expression in fetal, neonate, 3, 5, 8 weeks old rats and experimental OA. Our results showed that mitosis phases were observed in all normal cartilage studied, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Polysome profiling revealed that many components of ECM including fibronectin are translationally repressed in unchallenged chondrocytes despite relatively high mRNA levels. This repression is consistent with the low mitotic activity of the residing chondrocytes (49, 50). However, high mRNA abundance of Fn1 in unchallenged chondrocytes makes this gene a quick responder to different stimulus through protein abundance in OA cartilage.…”
Section: Discussionsupporting
confidence: 86%
“…Polysome profiling revealed that many components of ECM including fibronectin are translationally repressed in unchallenged chondrocytes despite relatively high mRNA levels. This repression is consistent with the low mitotic activity of the residing chondrocytes (49, 50). However, high mRNA abundance of Fn1 in unchallenged chondrocytes makes this gene a quick responder to different stimulus through protein abundance in OA cartilage.…”
Section: Discussionsupporting
confidence: 86%
“…The present data unquestionably raise the question of whether cellular proliferation may be responsible for the observed increase in the superficial chondrocyte numbers and the spatial remodeling of the cellular organization in early OA. Although proliferation of chondrocytes is a topic of controversy, many studies have shown that chondrocytes are in fact mitotically active (2, 26–33). In OA, fibrillation‐ or lesion‐associated cellular aggregation is thought to be related to chondrocyte proliferation (2, 10–12, 34).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of advanced OA cartilage samples, the investigators doubted the existence of chondrocyte cell division and, consequently, the existence of cell proliferation in OA (33). Observing mitoses as direct evidence of proliferation, they reported the absence of mitotic figures in cartilage with advanced OA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proliferation of chondrocytes has been suggested as the principal mechanism in cluster formation based on studies of 3 H-thymidine and/or bromodeoxyuridine incorporation and the detection of proliferation markers such as PCNA and Ki67 in experimental OA models [53,54]. Because mitotic figures have not been detected in either mature or OA articular cartilage [53], chondrocyte migration has been suggested as a contributor to cluster formation. Chondrocytes have the ability to migrate in vitro in response to cytokines and growth factors [55,56].…”
Section: Discussionmentioning
confidence: 98%